2016
DOI: 10.1007/s12032-016-0787-z
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of KRAS mutation status between primary tumor and metastasis in Chinese colorectal cancer patients

Abstract: Detection of KRAS mutation status is a routine clinical procedure for predicting response to anti-EGFR therapy in colorectal cancer (CRC) patients. Previous studies showed high concordance of KRAS mutation status in primary lesion and corresponding metastatic sites in CRC. However, the data were mostly from Caucasians. The aim of this study is to compare KRAS mutation and other molecules mutation status between primary tumor and corresponding metastatic lesion in Chinese patients with CRC. In this retrospectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 46 publications
3
15
0
1
Order By: Relevance
“…We might postulate that targeted therapy against HSP90/ Topo I molecules expressed on the tumor cells, could improve the effectiveness of CRC treatment. In the present study, the results concerning KRAS mutation in CRC are in agreement with literature (9,10,11,26). The frequency of KRAS mutation in CRC with lymph node metastasis, noted in the current study, was also observed by other authors (9,26).…”
Section: Discussionsupporting
confidence: 93%
“…We might postulate that targeted therapy against HSP90/ Topo I molecules expressed on the tumor cells, could improve the effectiveness of CRC treatment. In the present study, the results concerning KRAS mutation in CRC are in agreement with literature (9,10,11,26). The frequency of KRAS mutation in CRC with lymph node metastasis, noted in the current study, was also observed by other authors (9,26).…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, the sample size and follow-up time need to be expanded and extended. Interestingly, clinical trials have shown that the outcome of patients with wild-type KRAS is significantly better than that of patients with KRAS mutations [24,25]. Our study obtained similar results according to RAS status for poor PFS.…”
Section: Discussionsupporting
confidence: 80%
“…Tumor heterogeneity has been widely reported 23 - 26 . For example, the rate of discordance of KRAS mutation status between primary and metastatic tumors was about 20% in Chinese CRC patients according to our previous study 27 . In order to help explain the mechanism of inefficient predictive value of PD-L1 expression for benefit from anti-PD-1 treatment in CRC, we conducted this study to explore the clinicopathological and biomarker relevance and heterogeneity of PD-L1 expression within primary tumors and between primary and metastatic tumors in a relatively large CRC patient sample.…”
Section: Introductionmentioning
confidence: 78%